Factors associated with late antenatal care booking in selected health facilities of Zoba Maekel, Eritrea: a cross-sectional study - Tesfaldet Mekonnen Estifanos; Kiflu Teweldebrhan Sengal; Eden Efrem Tekleab; Futsum Abed Mehari; Issak Gebreezgiabhier Tesfagabr; Major Asefa Tesfay; Ghidey Gebreyohannes (BMC Pregnancy and Childbirth)
Abstract Background Antenatal care is a special care provided for pregnant women with the aim of preventing, detecting, and treating health problems in both the fetus and mother. Early antenatal care attendance promotes early detection and treatment of complications which result in proper management during delivery and puerperium. However, the majority of pregnant women in Eritrea initiate their ANC booking late. The study aims to assess factors associated with late ANC booking among pregnant mothers attending selected antenatal care services in Zoba Maekel, Eritrea. Method A health facility based cross-sectional study was conducted from February to March 2022 among 439 pregnant women. To select the study participants, a stratified two-stage cluster sampling method was employed and a predesigned and pretested questionnaire was used to collect data regarding factors associated with late antenatal booking. Binary logistic regression analysis was used to assess the association between the outcome variable and the independent variables and a P-value less than 0.05 was considered statistically significant. Result The prevalence of late antenatal care booking was 59% (95% CI 0.54–0.64). Those aged 20–34 years (AOR: 0.26; 95% CI: 0.15–0.44), 34 and above (AOR: 0.21; 95% CI: 0.11–0.33), and those who were unemployed (AOR: 0.45; 95% CI: 0.34–0.59) had decreased odds of late first ANV booking. Having family size of 4 and above (AOR: 2.25; 95% CI: 1.07–4.74), reside in rural areas (AOR = 2.20, 95%, CI: 1.38–3.50), from Muslim religion (AOR = 2.11, 95%, CI: 1.70–2.62), with gravida 2 to 4 (AOR = 2.11, 95%, CI: 1.70–2.62) and gravida 5 and above (AOR = 3.11, 95%, CI: 2.26–4.27) had higher odds of late antenatal care initiation. The odds of late ANC initiation was 1.62 among ANC visitors yet not accompanied by their husband to health center (AOR = 1.62, 95% CI 1.35–1.95). Conclusion This study showed that most pregnant women did not start ANC booking earlier. Further, the study indicated that younger age, rural settlements, family size ≥ 4, from Muslim religion, employees, gravida 4 to 9, and those who did not get husband/family support to ANC follow-up, were highly likely to initiate ANC booking late. Hence, it is crucial to provide health education on the timing of ANC among women of reproductive age. The community's awareness of the importance of receiving early ANC also needs to be promoted.